Design optimization of highly efficient spectrum-splitting and beam-concentrating diffractive optical element for lateral multijunction solar cells - 王进泽 叶佳声 黄庆礼 许信 李冬梅 孟庆波 杨国桢 (Chinese physics B, 2014)
Two improved algorithms are proposed to extend a diffractive optical element （DOE） to work under the broad spec- trum of sunlight. An optimum design has been found for the DOE, with a weighted average optical efficiency of about 6.8% better than that of the previous design. The optimization of designing high optical efficiency DOEs will pave the way for future designs of high-efficiency, low-cost lateral multijunction solar cells based on such a DOE.